HEADS AND TAILS: 30 MILLION YEARS OF THE AFAR PLUME - Furman T.; Rooney T.; Bryce J.; Hanan B.; Yirgu G.; Ayalew D. (My University, 2006)
Primitive recent mafic lavas from the Main Ethiopian Rift provide insight into the structure, composition and long-term history of the Afar plume. Modern rift basalts are mildly alkalic in composition, and were derived by moderate degrees of melting of fertile peridotite at depths corresponding to the base of the modern lithosphere (c.100 km). They are typically more silica-undersaturated than Oligocene lavas from the Ethiopia- Yemen continental flood basalt province, indicating derivation by generally smaller degrees of melting than were prevalent during the onset of plume head activity in this region. Major and trace element differences between the Oligocene and modern suites can be interpreted in terms of melting processes, including meltinduced binary mixing of melts from the Afar plume and those from three mantle end-member compositions (the convecting upper mantle and two enriched mantle sources). The Afar plume composition itself has remained essentially constant over the past 30 million years, indicating that the plume is a long-lived feature of the mantle. The geochemical and isotopic compositions of mafic lavas derived from the Afar plume support a modified single plume model in which multiple plume stems rise from a common large plume originating at great depth in the mantle (i.e. the South African superplume). © The Geological Society of London 2006.
Keywords: Oligocene; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен